2023
DOI: 10.3390/su15021548
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Emotional Values Embedded in Thai-Consumers’ Perceptions: Key Factors for the Sustainability of Traditional Confectionery Businesses

Abstract: The confectionery market in Thailand is being overpowered by Western confectioneries. This study proposes and verifies a model of the factors that define consumer behaviour towards traditional Thai confectioneries and consumer willingness to support them. In recent years, there has been a boom in posting various aspects of Thai youth culture, including confectionery, on social networking services (SNS), especially Instagram. In major Thai cities, such as Bangkok, stores are being built with ‘Insta-image’ in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…En otras palabras, se trata de cómo un producto puede generar emociones en las personas, ya sean positivas o negativas. Estas emociones pueden ser diversas e incluir sentimientos como entusiasmo, fidelidad, remordimiento o incluso aprensión (Oe et al, 2023). Algunos productos o servicios pueden hacer que los consumidores se sientan emocionados, felices o satisfechos.…”
Section: Valor Emocionalunclassified
“…En otras palabras, se trata de cómo un producto puede generar emociones en las personas, ya sean positivas o negativas. Estas emociones pueden ser diversas e incluir sentimientos como entusiasmo, fidelidad, remordimiento o incluso aprensión (Oe et al, 2023). Algunos productos o servicios pueden hacer que los consumidores se sientan emocionados, felices o satisfechos.…”
Section: Valor Emocionalunclassified
“…This study compliments the Gatica-Arias [ 19 ] study because the results presented here were derived from an in-person survey of Costa Rican consumers and finds roughly the same results. Lassoued [ 20 ] found that when Canadian consumers were asked about sustainability and GE technologies, over 50% responded positively to a range of GE sustainability factors. In Japan, Otsuka [ 21 ] shows that consumers view GE crops as less natural and more similar to genetically modified organisms.…”
Section: Introductionmentioning
confidence: 99%
“…After six pilot tests to check the wording of the questions, 26 questions were selected based on the hypothetical framework. All of the questions used a five-point Likert scale (Oe et al, 2023). A 5-point Likert scale was used for the survey.…”
Section: Introductionmentioning
confidence: 99%